Integrated Local and Coordinated Overvoltage Control to Increase Energy Feed-In and Expand DER Participation in Low-Voltage Networks - Alonso, Augusto Matheus dos Santos; De Oro Arenas, Luis; Brandao, Danilo; Tedeschi, Elisabetta; Marafao, Fernando Pinhabel (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Large amounts of active power injection by inverter-interfaced distributed energy resources (DER) is a common cause of overvoltage in low-voltage networks. Hence, local active and reactive power control (i.e., Volt/Watt and Volt/VAR, respectively) are adopted to limit voltage rise, leading to active power curtailment. This paper proposes an automatic control strategy to steer non-dispatchable (nd-DER) and dispatchable (d-DER) inverters in low-voltage networks, mitigating overvoltage through integrated local and coordinated Volt/Watt and Volt/VAR functionalities. Moreover, active power curtailment is avoided whenever possible. The method does not require i) the implementation of optimization algorithms or ii) knowledge about line impedance parameters or the location of DERs. The control approach exploits the power flow dispatchability of low-voltage networks comprising one point-of-common coupling with the distribution grid, allowing DERs close to the distribution transformer to also contribute to voltage regulation by only using a low-bandwidth communication link. Simulation results show the flexibilities of the proposed approach and demonstrate that active power injection can be increased by up to 25% for the considered scenario in comparison to conventional local Volt/Watt or Volt/VAR schemes. Experimental results based on a laboratory prototype with three inverter-interfaced DERs certify the applicability of the approach to real-life implementations.
Keywords: Distributed energy resources; Genetic algorithms; Inverters; Low voltage; Optimization; overvoltage; Reactive power; Reactive power control; reactive power control; Voltage control; voltage control